Isolation and characterization of verocytotoxin-producing Escherichia coli O157 from Turkish cattle - Aslantas, Ö; Erdogan, S; Cantekin, Z; Gülaçti, I; Evrendilek, GA (Elsevier, 2006)
The objective of this study was to collect rectal swabs from the cattle in a slaughterhouse located in Hatay (Turkey) immediately after slaughter for the isolation and characterization of verotoxin-producing Escherichia coli O157 in each month during a 1-year period. The rectal swab samples were analyzed for the isolation of E. coli O157 through preenrichment, immunomagnetic separation and selective plating on CT-SMAC agar. E. coli O157 was isolated from 77 (13.6%) of the samples. The presence of E. coli O157 changed during a 1-year period, in that the occurrence of E. coli O157 was the highest in July and November and lowest in February. A total of 66 isolates out of 77 were seroytpe O157:H7 and 11 were serotype O157:NM. PCR analysis of E. coli O157 virulence genes revealed that all O157:H7/NM were positive for rbf(O157), 74 positive for EhlyA, 72 positive for eaeA, 62 positive for vtx2, and 3 positive for both vtx1 and vtx2. It was presented by cytotoxicity tests that many of E. coli O157 isolates showed high cytotoxicity on Vero cells. All of the isolates containing EhlyA showed enterohaemolysin production. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Escherichia coli O157; Turkey; cattle; IMS; PCR